القدرة العضلية للرجلين للاعب الحر وعلاقتها بدقة استقبال الإرسال بالكرة الطائرة - طاهر، حبيب علي; حافظ، حاتم فليح (جامعة بابل - كلية التربية الرياضية, 2011)
تطرق الباحثان في الباب الأول إلى مقدمة البحث وأهمية من خلال التركيز على القدرة العضلية والدقة باعتبارهما صفتان حركيتان مهمتان ولهما دور بارز في تطوير تكنيك مستوى الرياضي كما تطرقا إلى اللاعب الحر في الكرة الطائرة وأهميته في استقبال الإرسال ودوره الفعال في المهارات الدفاعية ومنها مهارة استقبال الإرسال وأهميتها في الإعداد الصحيح للهجوم فضلا عن مشكلة البحث التي تنحصر في التركيز على القدرة العضلية للرجلين للاعب الحر وأهميتها في دقة استقبال الإرسال ومدى تأثيرها على تحركاته الدفاعية. \ كما هدفت الدراسة إلى: \ التعرف على علاقة الارتباط بين القدرة العضلية للرجلين للاعب الحر ودقة واستقبال الإرسال بالكرة الطائرة \ وافترض الباحثان: \ ان هناك علاقة ذات دلاله معنوية بين القدرة العضلية للرجلين للاعب الحر ودقة استقبال الإرسال بالكرة الطائرة. \ أما في الباب الثاني فقد تطرق الباحثان: \ إلى الدراسات النظرية ومنها. \ القدرة الفعلية للرجلين ودقة استقبال الإرسال للاعب الحر بالكرة الطائرة. \ أما في الباب الثالث فقد استخدم الباحثان المنهج الوصفي بأسلوب المسح والعلاقات الارتباطية واشتمل على عينه البحث والأدوات المستخدمة والاختبارات والتجربة الاستطلاعية والأسس العلمية للاختبارات والوسائل الاحصائية المناسبة لمعالجة النتائج. \ أما في الباب الرابع. \ فقد قام الباحثان بعرض نتائج اختبارات القدرة الفعلية ودقة استقبال الإرسال كما عرضا علاقة الارتباط بين القدرة العضلية ودقة استقبال الإرسال بالكرة الطائرة. وتحليلها ومناقشتها. \ وفي الباب الخامس \ توصل الباحثان إلى الاستنتاجات التالية: \ 1.\ يمتلك اللاعب الحر لكل نادي في دوري النخبة بالكرة الطائرة قدره عضلية ودقة في استقبال الارسال. \ 2.\ توجد علاقة ارتباط مضمونة بين القدرة العضلية للرجلين للاعب الحر ودقة استقبال الإرسال بالكرة الطائرة. \ وبناءا على ما توصل إليه الباحثان من استنتاجات يوصيان بما يلي: \ 1.\ التأكيد على عناصر اللياقة البدنية الأخرى المتمثلة بالقوة والمرونة والرشاقة والتواثق لتأثيرها في تطوير الأداء الدفاعي للاعب الحر. \ 2.\ التأكيد على تمارين الدقة والقدرة العضلية باستخدام وسائل مساعدة لأداء الاختبارات التي تعني بذلك والتأكيد على استخدام الدقة بإتباع أسلوب العمل الخارجي مع بقية عناصر اللياقة البدنية للحصول على الخبرة الحركية Touched researchers in the door first to the forefront of research and the importance of focusing on the ability muscle and precision as qualities Hrkitan tasks and have a prominent role in the development of technique level sports as they talk about the player free in volleyball and 'its. importance in receiving transmissions and its effective role in the skills of defense and of skill -receive the tmsmission and its importance in the correct setting of the attack as well as the research problem, which is focused on the ability of the muscle men of the free player and its importance in the accuracy of the transmission and reception. over the impact on the defensive moves. \ The study aimed to: \ Identify the correlation between the ability of muscle men free of the player and the accuracy of transmission and reception of the ball flight. \ The researchers assumed: \ There is a significant relationship between the moral capacity of the muscle men of tire player receiving a free and accurate transmission volleyball. \ In Part II has touched the researchers: - \ To theoretical studies of \ Actual capacity of the two men and the accuracy of transmission of the player receiving the ball free plane. \ In -Part Three researchers have used descriptive method in a manner scanning and connectivity relations and included a sample and the tools used and the tats and exploratory experience and the scientific basis for the tests and appropriate statistical methods for processing the results. \ In Part IV. \ The researchers have \ Presented the results of tests of ability and accuracy of the actual transmission and reception presented the correlation between muscle power and accuracy of sending the ball to receive the aircraft. Analyzed and discussed. \ In section V \ Researchers reached the following conclusions: \ 1.\ has a free player for each club in the league of elite volleyball muscle and accuracy in receiving the transmission. \ 2.\ no guaranteed correlation between the ability of the muscle men of the player receiving a free and accurate transmission volleyball. \ Based on Matousel the conclusions of the researchers recommend the following: \ 1.\ emphasis on other fitness components of strength, flexibility, agility and Altoathag to their influence in the development of the defensive performance of the player free. \ 2.\ emphasis on precision and power exercises using muscle and aids to perform the tests, which means that the emphasis on the use of precision by following the. method' of external work with the rest of the elements of fitness for a kinetic experience.
775778
Keywords: العراق -- التربية البدنية -- الكرة الطائرة -- القدرة العضلية للرجلين -- اللاعب الحر -- مهارات الارسال -- اللاعب الحر في دوري النخبة لعام 2011م